Climate change mitigation through intensified pasture management: Estimating greenhouse gas emissions on cattle farms in the Brazilian Amazon. (20th September 2017) - Bogaerts, Meghan; Cirhigiri, Lora; Robinson, Ian; Rodkin, Mikaela; Hajjar, Reem; Costa Junior, Ciniro; Newton, Peter
Abstract: Cattle ranching in Brazil is a key driver of deforestation and greenhouse gas (GHG) emissions. The Brazilian government plans to reduce national GHG emissions by at least 36%, partly by reducing emissions in the livestock sector through strategies such as intensification, pasture improvement, and rotational grazing. In response, sustainability programs promoting these practices have begun operation. Though studies have previously investigated aspects of GHG emissions and sequestration in improved pastures, they have not linked improvements with programmatic interventions. We surveyed 40 cattle ranchers located in the Brazilian Amazon biome to investigate how GHG emissions differed between farms participating in livestock sustainability programs with intensified production and farms not participating in these programs. We found that participating farms produced 8.3 kg of CO2 e/kg of carcass weight (CW) less than did non-participating farms, which represents 19% fewer emissions. Farms that had participated in a sustainability program for at least two years showed larger differences in emissions: 19.0 kg of CO2 e/kg CW less for program farms compared with their counterparts, or 35.8% fewer emissions. Key drivers of the total CO2 e/kg CW in all farms were enteric fermentation and manure management. This paper provides farm-level data supporting intensification as a possible strategy to reduce emissions per kilogram of beef produced, and suggests that future research efforts should focus on long-term impacts of intensification and expand metrics for success beyond GHG calculations. Highlights: Intensification of pasture-raised beef can reduce per kilogram carbon emissions. Sustainability programs and certifications encourage intensification. Key drivers of carbon emissions are enteric fermentation and manure management. Emissions reductions are greatest in relatively more established programs. Sustainability programs in the Brazilian Amazon all incorporate intensification.